Progress in Neonatal Neurology with a Focus on Neuroimaging in the Preterm Infant - de Vries, Linda S.; Benders, Manon J. N. L.; Groenendaal, Floris (Neuropediatrics, 2015)
There have been tremendous changes in the methods used to evaluate brain injury in the preterm infant in the past 30 years. In particular, major improvements have been made in how we use neuroimaging techniques and now magnetic resonance imaging (MRI) is used more often and considered complimentary to routine and sequential cranial ultrasound. The focus has shifted from severe lesions such as large intraventricular and parenchymal hemorrhages and cystic periventricular leukomalacia to assessing and understanding the etiology of more subtle noncystic white matter injury, punctate hemorrhage, and cerebellar lesions. The more severe lesions that dominated the early period of preterm neonatal brain imaging occur less frequently but are still associated with major disabilities, such as, cerebral palsy, while subtle white matter injury and cerebellar lesions are more often associated with cognitive and behavioral problems, which have become the most prevalent issues among the survivors of extremely preterm birth.
Keywords: neuro-imaging; cranial ultrasound; MRI; cerebral palsy